Accuracy and criterion-related validity of the 20-M shuttle run test in well-trained young basketball players - Stojanovic, M. D.; Calleja-Gonzalez, J.; Mikic, M.; Madic, D. M.; Drid, P.; Vuckovic, I.; Ostojic, S. M. (Montenegrin Journal of Sports Science and Medicine, 2016)
The purpose of the present study was to evaluate the specificity of a 20-m shuttle run test (SRT) as a measure of maximal oxygen consumption (VO2max) in young well-trained basketball players. Thirty-four volunteers (mean ± SD; age 15.74 ± 1.23 years, height 187.61 ± 7.95 cm, body mass 74.09 ± 11.61 kg; training experience 6.30 ± 2.15 years) participated in the study. The 20-m shuttle run test was performed wearing a portable gas analyzer (K4b2, Cosmed) to measure VO2max during the test. SRT-derived VO2max underestimated directly measured values (48.91 ± 4,11 vs 55.45 ± 4.98). Mean bias was 6.54 ± 3.89 ml kg-1 min-1 (95% CI- 5.18 to 7.90 ml kg-1 min-1 ). Typical error of the estimate was 3.85 ml/kg/min-1 (95% CI- 3.10 to 5.10 ml kg-1 min-1 ; ES= 0,77). There was a moderate correlation between VO2max directly measured and estimated by SRT (r= 0.65; 95% CI- 0.40 to 0.81, power = 0.84, p < 0.01). Although very popular among coaches, it seems that SRT is not an appropriate field test to measure maximal oxygen consumption in young well-trained basketball players.